Circulating MicroRNAs: Potential and Emerging Biomarkers for Diagnosis of Human Infectious Diseases - Verma, Parmila; Pandey, Rajan K.; Prajapati, Priyanka; Prajapati, Vijay K. (Frontiers in Microbiology, 2016)
MicroRNAs (miRNAs) are evolutionary conserved, small non-coding RNA with size ranging from 19 to 24 nucleotides. They endogenously regulate the gene expression at the post transcriptional level either through translation repression or mRNA degradation. MiRNAs have shown the potential to be used as a biomarker for the diagnosis, prognosis, and therapy of infectious diseases. Many miRNAs have shown significantly altered expression during infection. The altered expression of miRNA level in an infected human can be identified by the use of advanced diagnostic tools. In this review, we have highlighted the use of miRNA as an emerging tool for the identification of the human infectious disease. Till date, several miRNAs have been reported as a molecular biomarker in infectious diseases, such as miRNA-150 and miRNA-146b-5p in human immunodeficiency virus (HIV); miRNA-122, miRNA-21, and miRNA-34a in hepatitis; miRNA-361-5p and miRNA-29c in tuberculosis; miRNA-16 and miRNA-451 in malaria and miRNA-181 in Helicobacter pylori infection. The diagnosis of infection with the help of a biomarker is a non-invasive tool that has shown to have a key role in early diagnosis of infection. The discovery of circulating miRNA in the blood of infected patients has the potential to become a powerful non-invasive biomarker in coming future.